Cross Flow Analysis over the Jet Pumps of a BWR-5 Reactor - G. Soto-Mendoza; A. Armenta-Molina; S. Pérez-Montejo; L.H. Hernández-Gómez; P. Ruiz-López; G.M. Urriolagoitia-Calderón; J.A. Beltrán-Fernández (Science and Technology of Nuclear Installations)
The recirculation system of a BWR-5 has 20 jet pumps. They are submerged in water in the cylindrical annular zone of the reactor. Their main function is the development of a forcing flow through the nuclear core. It increases the power of the reactor compared with the one obtained by natural circulation. These components have an important safety function in the operation of the reactor. In accordance with document BWRVIP-41 R4, it was concluded that the vibration induced by cross flow over the jet pump assemblies is one of the degradation mechanisms of such pumps. In this paper, the vibration induced by the cross flow at a jet pump assembly BWR-5 was analyzed. A numerical approach was developed. The natural frequencies were obtained, considering the Fluid-Structure Interaction (FSI). The first natural frequency was 25.7 Hz. A Computational Fluid Dynamics (CFD) analysis was carried, in conjunction with the Power Spectral Density (PSD). A frequency of vortex generation of 0.48 Hz was obtained. A vortex generation analysis was carried out with the Q-criteria. The results showed that resonance conditions are unlikely. Therefore, the structural integrity of the jet pump assemblies is maintained.